Plug In Electric Vehicles in Smart Grids: Energy Management - Rajakaruna, Sumedha; Shahnia, Farhad; Ghosh, Arindam (Springer, 2014)
This book highlights the cutting-edge research on energy management within smart grids with significant deployment of Plug-in Electric Vehicles (PEV). These vehicles not only can be a significant electrical power consumer during Grid to Vehicle (G2V) charging mode, they can also be smartly utilized as a controlled source of electrical power when they are used in Vehicle to Grid (V2G) operating mode. Electricity Price, Time of Use Tariffs, Quality of Service, Social Welfare as well as electrical parameters of the network are all different criteria considered by the researchers when developing energy management techniques for PEVs. Risk averse stochastic energy hub management, maximizing profits in ancillary service markets, power market bidding strategies for fleets of PEVs, energy management of PEVs in the presence of renewable energy in distribution lines or microgrids and loss minimization in distribution networks based on smart coordination approaches using real time energy prices are some of the attractive and novel topics explored in this book. It will be an excellent reference for graduate students, researchers and industry professionals who are interested in getting a snapshot view of today’s latest research on applying various smart energy management strategies for smart grids with high penetration of PEVs.